2010
DOI: 10.1073/pnas.1013805107
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine TGF-β and stromal cell-derived factor-1 (SDF-1) signaling drives the evolution of tumor-promoting mammary stromal myofibroblasts

Abstract: Much interest is currently focused on the emerging role of tumorstroma interactions essential for supporting tumor progression. Carcinoma-associated fibroblasts (CAFs), frequently present in the stroma of human breast carcinomas, include a large number of myofibroblasts, a hallmark of activated fibroblasts. These fibroblasts have an ability to substantially promote tumorigenesis. However, the precise cellular origins of CAFs and the molecular mechanisms by which these cells evolve into tumor-promoting myofibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
695
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 725 publications
(749 citation statements)
references
References 53 publications
21
695
0
12
Order By: Relevance
“…While it is conceivable that such paracrine signalling mechanisms that activate fibroblasts in vivo could be derived from immune cells, there is also evidence indicating direct regulation by neoplastic cells: co-culture of fibroblasts with either melanoma cells or oral squamous cell carcinoma cells induces pro-inflammatory gene expression in fibroblasts that includes CXCL1 and CXCL2 [59,60]. Activation of CAFs can also be accelerated by autocrine signalling: Kojima et al reported that autocrine TGF-β and SDF-1α/CXCL12 chemokine signalling result in activation of mammary CAFs, but the in vivo molecular signals that trigger these inflammatory pathways in CAFs remain unknown [61]. TGF-β and SDF-1α/CXCL12 may have an additional role in the recruitment of pro-inflammatory CAFs from bone marrow: In a model of induced gastric cancer, Quante et al reported that CAFs recruited into gastric tumours from bone marrow express a pro-inflammatory gene signature that includes CXCL1, CCL5, OPN, IL-6, IL-1β, CXCL12, and TNF-α [40].…”
Section: Activation By Paracrine Signallingmentioning
confidence: 99%
“…While it is conceivable that such paracrine signalling mechanisms that activate fibroblasts in vivo could be derived from immune cells, there is also evidence indicating direct regulation by neoplastic cells: co-culture of fibroblasts with either melanoma cells or oral squamous cell carcinoma cells induces pro-inflammatory gene expression in fibroblasts that includes CXCL1 and CXCL2 [59,60]. Activation of CAFs can also be accelerated by autocrine signalling: Kojima et al reported that autocrine TGF-β and SDF-1α/CXCL12 chemokine signalling result in activation of mammary CAFs, but the in vivo molecular signals that trigger these inflammatory pathways in CAFs remain unknown [61]. TGF-β and SDF-1α/CXCL12 may have an additional role in the recruitment of pro-inflammatory CAFs from bone marrow: In a model of induced gastric cancer, Quante et al reported that CAFs recruited into gastric tumours from bone marrow express a pro-inflammatory gene signature that includes CXCL1, CCL5, OPN, IL-6, IL-1β, CXCL12, and TNF-α [40].…”
Section: Activation By Paracrine Signallingmentioning
confidence: 99%
“…In breast cancer, TGFβ1 is upregulated compared to its adjacent nonmalignant tissue and it impacts on various cells of the tumor microenvironment. In the tumor stroma, TGFβ1 gets secreted by tumor‐associated macrophages and CAFs (Kojima et al ., 2010; Yu et al ., 2014). It has been shown that TGFβ1 directly acts on the basal‐like breast tumor cell line MDA‐MB‐231 and that this drives metastatic processes of breast cancer cells by its binding to TGFBR2 (Willis et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…19 A huge variety of cell types such as epithelial cells, mesenchymal stem cells, resident fibroblasts or endothelial cells have been reported to be able to transdifferentiate into CAFs through epithelial-mesenchymal transition (EMT), mesothelial-to-mesenchymal transition (MMT), or endothelial-mesenchymal transition (EndMT). [20][21][22][23][24] All these models for CAF development assume exogenous stimuli that initiate transformation and, in most cases, are thought to be sent from adjacent cancer cells in form of growth factors, such as TGF-ß and CXCL12. 23 There is experimental evidence that the CAF phenotype can also be initiated by intrinsic factors.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] All these models for CAF development assume exogenous stimuli that initiate transformation and, in most cases, are thought to be sent from adjacent cancer cells in form of growth factors, such as TGF-ß and CXCL12. 23 There is experimental evidence that the CAF phenotype can also be initiated by intrinsic factors. In particular depletion of tumor suppressor genes was reported to convert normal fibroblasts to CAFs.…”
Section: Discussionmentioning
confidence: 99%